THE FINANCIAL LITERACY CONCEPT - IMPROVEMENT OF CONDITIONS IN THE REPUBLIC OF SERBIA (Heritage, 2024)
The paper analyzes the concept of financial literacy and the importance of national strategies as a pillar of financial literacy development. The authors start from the fact that the concept of financial literacy includes knowledge, education, abilities, competence and responsibility at the same time. The focus is on knowledge, the ability to apply knowledge, as well as the existence of self-confidence in people to undertake financial actions, risks, facing challenging situations and recognizing opportunities in the business environment. In other words, financial literacy means that the knowledge and skills we possess in the field of finance serve us in the process of understanding finances and making the right decisions using available information. Good financial education and good financial understanding of individuals dictates their quality and adequate financial decisions. In addition, financial education and financial literacy are gaining importance and importance, which confirms the interest of the professional and scientific community, which is reflected in the increased number of published works and research at the national and international level. Recent history, the world economic crisis, the pandemic caused by the Covid-19 virus, war events in Ukraine, rapid technological changes and innovations represent a "trigger" for the development of financial literacy. If there are no national strategies, regulatory bodies should find an effective mechanism for implementing the concept of financial literacy either through existing action plans/national strategies or by forming working groups that will deal with this topic in a new strategic and national framework.
Keywords: financial literacy, financial education, financial ability, financial knowledge, national strategies